Performance of Rapid Seismic Safety Assessment Methods on Estimation of Seismic Vulnerability of Relatively New RC Buildings Affected by the February 2023 Türkiye Earthquake Sequence - KOÇAK, PINAR İNCİ; SEÇKİN, EDİP; COŞKUN, ERDAL; TÜRK, AHMET MURAT; İlki, Alper (Taylor & Francis Ltd., 2025)
This study evaluates the performance of five rapid seismic safety assessment methods for relatively new reinforced concrete (RC) buildings affected by February 2023 T & uuml;rkiye earthquakes. Methods demonstrated reasonable performance in grading seismic vulnerabilities, whereas approaches incorporating deformation-based criteria, structural characteristics of newer buildings and seismic demand exhibited better accuracy. Methods, originally calibrated for older buildings and moderate earthquakes, are prone to under- or over-estimations of vulnerabilities. This underscores the need for refinements of methods which do not consider the characteristics of newer buildings and strong ground motions beyond the design level of earthquakes.
Keywords: Earthquake Damage; February 2023 Earthquakes; Rapid Seismic Assessment; Reinforced Concretebuildings; Seismic